Qualidade da informação contábil no mercado de capitais brasileiro: efeito da implementação do novo relatório do auditor independente - Queiroz, Matheus Marcos Morais de (2020)
The independent audit of financial statements, as an activity, has the role of being the agent between the information prepared by the administrator and the user of the information (Healy & Palepu, 2001). In recent decades, however, after corporate scandals involving large companies, regulators have mobilized to restore market confidence through standards that would enable audit reports with a higher level of transparency and information. In January 2015, after a restructuring process that was called the Auditor Reporting Project, the International Auditing and Assurance Standards Board (IAASB) released new standards that brought relevant changes to the independent auditor's report. Among the innovations brought about in the structure of the auditor's report, the main one was the inclusion of Key Audit Matters (KAM), called in Brazil as Main Audit Matters (PAA). In this sense, the objective of this work was to analyze the influence of the implementation of the New Auditor's Report (NRA) on the earnings quality in the Brazilian capital market. As proxies for the earnings quality, this research involved the attributes of earnings persistence (Dechow & Schrand, 2004), conservatism (Ball & Shivakumar, 2005), and earnings management (Pae, 2005). Based on data from 216 non-financial companies listed on B3 (Brazil, Bolsa, Balcão), such proxies were estimated for the period before (2013-2015) and after (2016-2018) the implementation of the NRA. The results showed that there was an improvement in the earnings quality related to the conservatism attribute after the implementation of the NRA; earnings persistence and earnings management, on the other hand, did not indicate improvement results. Additionally, in companies where matters of an expense nature (PAAs) were relevant in conducting the auditor's work and reported by him to the market, a greater incidence of earnings management was found. The research contributes to the literature of the earnings quality and highlights the relevance of regulatory processes in the segment of independent auditing, as well as their reflection in the financial statements. Also, the findings can assist stakeholders in decision making based on a better understanding of the dimensions of the independent auditor's report, in addition to providing regulatory bodies with useful information for future regulatory processes.